1999
DOI: 10.1086/312380
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Properties of SGR 1900+14 Bursts

Abstract: We study the statistics of soft gamma repeater (SGR) bursts using a database of 187 events detected with BATSE and 837 events detected with the Rossi X-Ray Timing Explorer Proportional Counter Array; all events are from SGR 1900+14 during its 1998-1999 active phase. We find that the fluence or energy distribution of bursts is consistent with a power law of index 1.66, over 4 orders of magnitude. This scale-free distribution resembles the Gutenberg-Richter law for earthquakes and gives evidence for self-organiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
88
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(115 citation statements)
references
References 26 publications
24
88
2
Order By: Relevance
“…The waiting time distribution can be fit by a wide lognormal distribution with a mean T waiting = 34 ± 11 s and a scatter of 2.3 s < T waiting < 496 s. At the peak of activity, the waiting time between subsequent bursts decreases to a time scale comparable to the duration of individual spikes, so that the bursts can be considered as either separate events or as parts of the "multispike" flares. This behavior is similar to the one observed in SGR bursts (Gögüş et al 1999). At the same time, the observed scatter of the waiting times is larger than the one found in the RXTE observations of 1E 2259+586 by Gavriil et al (2004), who found that the waiting time between subsequent bursts is always larger than 1 s (≥10 times longer than the typical burst duration).…”
Section: Statistical Study Of the Burst Propertiessupporting
confidence: 86%
See 2 more Smart Citations
“…The waiting time distribution can be fit by a wide lognormal distribution with a mean T waiting = 34 ± 11 s and a scatter of 2.3 s < T waiting < 496 s. At the peak of activity, the waiting time between subsequent bursts decreases to a time scale comparable to the duration of individual spikes, so that the bursts can be considered as either separate events or as parts of the "multispike" flares. This behavior is similar to the one observed in SGR bursts (Gögüş et al 1999). At the same time, the observed scatter of the waiting times is larger than the one found in the RXTE observations of 1E 2259+586 by Gavriil et al (2004), who found that the waiting time between subsequent bursts is always larger than 1 s (≥10 times longer than the typical burst duration).…”
Section: Statistical Study Of the Burst Propertiessupporting
confidence: 86%
“…The observed fluence-duration correlation is different from the one observed in 1E 2259+586 (F ∼ T 0.54±0.08 by Gavriil et al 2004) and instead resembles more the fluence-duration relation of SGR bursts, e.g. F ∼ T 1.13 in SGR 1900+14, (Gögüş et al 1999) (note that the correlation F − T correlation is not very tight both in our case and in the case of SGR 1900+14, so that the two relations are consistent).…”
Section: Statistical Study Of the Burst Propertiescontrasting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, soft γ-ray repeaters also have a power-law energy frequency distribution 25,26 with α E ∼ 1.5. A power-law distribution of occurrence frequency is characteristic of a SOC system 20 .…”
Section: Lines Inmentioning
confidence: 99%
“…The importance of ITDs cannot be overstated, as is the case for other different astrophysical sources, such as the Sun (e.g., Wheatland 2000;Aschwanden & McTiernan 2010), and outbursting magnetars (Göǧüş et al 1999(Göǧüş et al , 2000Gavriil et al 2004). In the case of GRBs a number of papers have investigated this property (McBreen et al 1994;Norris et al 1996).…”
Section: Introductionmentioning
confidence: 99%